2e réunion du comité international préparatoire du 12e festival mondial de la jeunesse et des étudiants (Union Internationale des Étudiants, 1984)
Art with colourful stripes coming together to form the world festival of youth and students' flower logo; grey background Poster advertising committee meeting ahead of the 12th world festival of youth and students, held in Sofia, April 1984 PO-0283